2012
DOI: 10.5851/kosfa.2012.32.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Three Candidate Genes Affecting Fatty Acid Composition in Pigs

Abstract: The association of three candidate genes, fatty acid synthase (FASN), microsomal triglyceride transfer protein (MTTP) and fatty acid binding protein 3 (FABP3), with fatty acid (FA) composition in Duroc pigs was investigated. Identified single nucleotide polymorphisms (SNPs) were used for polymerase chain reaction-restriction fragment length polymorphism genotyping. The c.265C>T SNP of FASN gene was significantly associated with high levels of palmitoleic acid (C16:1) (p<0.05), oleic acid (C18:1) (p<0.01), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The associations observed in the present work between FASN mutation and palmitoleic and stearic acids are concordant with the evidence reported by Maharani et al (2012) in Duroc pigs, where CC homozygotes had lower palmitoleic and higher stearic contents than CT pigs. The same polymorphism has also been investigated by Renaville et al (2018), but few associations with FA composition of backfat and leg fat were observed.…”
Section: Association Studysupporting
confidence: 93%
“…The associations observed in the present work between FASN mutation and palmitoleic and stearic acids are concordant with the evidence reported by Maharani et al (2012) in Duroc pigs, where CC homozygotes had lower palmitoleic and higher stearic contents than CT pigs. The same polymorphism has also been investigated by Renaville et al (2018), but few associations with FA composition of backfat and leg fat were observed.…”
Section: Association Studysupporting
confidence: 93%
“…Stearic acid (C18:0) is a saturated fatty acid which is needed in human diet, it does not rise plasma Low density lipoprotein cholesterol (Baer et al, 2003) as other saturated fatty acids do. Stearic acid and unsaturated fatty acids are considered to be desirable fatty acids (DFA) (Sebsibe, 2008) as they contribute to the increased activity of hepatic low density lipoprotein (LDL) receptor resulting into reduced circulating concentration of Low density lipoprotein-cholesterol (LDL-C) also known as bad cholesterol (Maharani et al, 2012). They present benefits to human health, stearic acid and unsaturated fatty acids get beneficial effect because they protect against cardiovascular diseases (Kaić and Mioč, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Unsaturated fatty acids are also grouped into monounsaturated fatty acids and polyunsaturated fatty acids (Hidayati et al, 2015). High consumption of unsaturated fatty acids presents healthy benefits because they accelerate activity of hepatic low density lipoprotein (LDL) receptor which reduces circulating concentration of LDL-cholesterol (Maharani et al 2012). High intake of saturated fatty acids has been linked with cardiovascular diseases and cancer (Hidayati et al;Kaić and Mioč, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al [ 16 ] reported higher levels of C16:1 and C18:1 in Korean native pigs crossed with Yorkshire pigs, with the CC or CT genotype (c.265C>T) and AA or AC (c.6545A>C) in comparison to the TT and CC genotypes, respectively. The effect of c.265C>T polymorphism (exon 4) was also analyzed by Maharani et al [ 27 ], who confirmed a higher proportion of C16:1, C18:1 and MUFA and lower contents of PUFA, including C18:2 and C18:3, in Duroc heterozygotes than in CC homozygotes. Our study also indicates that two polymorphisms (c.-2335C>T and c.*264A>G) of this gene are associated with the FA composition in back fat and longissimus thoracis et lumborum tissues.…”
Section: Resultsmentioning
confidence: 91%